DILEMMA: ENVIRONMENTAL LAW AND ANTHROPOCENTRISM - Abduazimova, Z.A. (Educational Research in Universal Sciences, 2023)
The article deals with issues affecting such characteristics of the socio-legal state as “ecology” and “anthropocentrism”. The author defines the factors of their influence on the general social structure of the state as priority areas of modern development. In addition, the author emphasizes that these concepts are consistently used by the legislator to determine certain goals of state and social policy, as they serve as an expression of the views of certain social groups and reflect some aspects of the formation of society.